Clinical advances on Bronchial Asthma. Changing perceptions. - Iris González Morales; Dianelis Sierra Martínez; Beatriz Home López Viera (Medisur)
Bronchial Asthma brepresents an important health problem worlwide due to the increment of its incidence in the last years. The general mortality is low in regard to morbidity but it could be potencially lethal. It is consider a frequent disease in our country when it is found in patients older than 15 years old and female sex is more prevalent than the male one. It has influence upon not only the ill person but also in the family ad society. The sanitary education is an important aspect for the correct control of sick patients. Within the following paper it is our intention to update the knowledge about this disease through a bibliographic revision. Epidemiology, physiopathology, classification, complementary explorations, as well as the factors that must be paid attention on its treatment are found among the processed aspects, all which will serve for consultation not only for students but also for professionals of the medical science branch.